The Tissue Systems Pathology Test Enabled Detection of Missed Prevalent High-Grade Dysplasia in a Presumed Clinically Low-Risk Patient With Nondysplastic Barrett's Esophagus - Breanna Dobberpuhl; Falak Hamo; Salih Samo (ACG Case Reports Journal, 2026)
Clinical guidelines recommend the use of histopathology and segment length to risk stratify patients with Barrett's esophagus (BE), the only known precursor of esophageal adenocarcinoma (EAC). However, these clinicopathologic factors have limited ability to accurately identify patients with nondysplastic BE (NDBE) who may be at high risk of progression. The tissue systems pathology-9 (TSP-9) test (TissueCypher) is clinically validated to predict the risk of progression of BE to high-grade dysplasia (HGD) or EAC within 5 years. This case report highlights the clinical utility of TSP-9 test to identify high-risk patients with NDBE and inform shared decision making to prevent progression to HGD/EAC.